Water-Soluble Ruthenium (II) Complex Derived From Optically Pure Limonene and Its Microencapsulation Are Efficient Tools Against Bacterial Food Pathogen Biofilms: Escherichia coli, Staphylococcus aureus, Enteroccocus faecalis, and Listeria monocytogenes - Khelissa, Simon; El Fannassi, Yousra; Mechmechani, Samah; Alhuthali, Sakhr; El Amrani, Mohamed Amin; Gharsallaoui, Adem; Barras, Alexandre; Chihib, Nour-Eddine (Frontiers in Microbiology, 2021)
Bioactive aminooxime ligands based on optically pure (R)-Limonene have been synthesized in two steps. Their Ruthenium (II) cationic water-soluble complex was prepared by a reaction between dichloro (para-cymene) Ruthenium (II) dimers and aminooxime ligands in a 1:2 molar ratio. Antibacterial and antibiofilm activities of the synthetized complex were assessed against Escherichia coli, Staphylococcus aureus, Listeria monocytogenes and Enterococcus faecalis. The results revealed that the Ruthenium (II) complex has higher antibacterial and antibiofilm activities in comparison to free ligands or the enantiopure (R)-Limonene. Moreover, microencapsulation of this complex reduced its cytotoxicity and improved their minimum inhibitory concentration and antibiofilm activity towards the considered bacteria. The Ruthenium (II) complex targets the bacterial cell membrane which leads to rapid leakage of intracellular potassium. Our study suggests that the developed Ruthenium (II) complexes could be useful as an alternative to conventional disinfectants.